Program Tahfiz Al-Qur'an Anak Usia Dini di TK Qurrota A'yun Yogyakarta - Wahyu Purwasih (UIN Raden Mas Said Surakarta, 2020)
This paper presents the implementation of the Tahfiz al-Qur'an program at Qurrota A'yun Kindergarten Yogyakarta. The subjects in this study were students of class B TK Qurrota A'yun Yogyakarta. The research method used is descriptive qualitative research method. Namely studying the meaning conveyed by respondents about problems or research issues through interview techniques, observation and documentation that the implementation of taáhfiz at Qurrota A'yun Kindergarten has several bases, namely philosophical, juridical, psychological, operational, and religious bases. The aim of implementing the tahfiz program at Qurrota A'yun Kindergarten Yogyakarta is to bring children and parents closer to the Al-Qur'an. The methods used in the tahfiz program at Qurrota A'yun Yogyakarta Kindergarten are the talaqqi method and the movement method. Program implementation is also influenced by several supporting and inhibiting factors. Supporting activities for the tahfiz program include tahfizcompetitions, playing murotals, and tahsin activities for all educators.